Mid-term outcomes of a smoking cessation program in hospitalized patients in Türkiye - Esin B. Konyalıhatipoğlu; Dilek Karadoğan; Tahsin Gökhan Telatar; Ünal Şahin (Tobacco Induced Diseases, 2024)
Introduction 'Teachable moments', such as inpatient treatment periods, can be turned into opportunities for smokers to acquire healthy living behaviors. This study was conducted to evaluate outcomes of smoking cessation interventions at an inpatient hospital setting.